AIR POLLUTION ESTIMATION IN ERBIL CITY CENTER USING BOX MATHEMATICAL MODEL - SHARIF, SALAH FARHAN A.; ANJEL, HASSAN ABDULWAHAB (Journal of Duhok University, 2021)
Erbil city center, topographically, is a low basin surrounded by highlands from all sides and is characterized as relatively humid weather during the autumn, winter and spring days. These factors with the increasing number of cars in the street, added to the vast number of private electric generators using poor quality of fuels caused the high level of air pollution in the basin and black clouds over the city. In this paper, the concentration of accumulated pollutants was estimated at different points by using a known mathematical model called “Fixed Box Model”. This mathematical model was developed and processed, by researchers, using computer mat lab to calculate the concentrations of pollutants in Erbil’s city center at any time of the day in different levels. The collected data of the contributing cars, trucks and electric generators were processed by the developed model and shows that the accumulated pollutants, on the breathing level 4 hours after the morning rash time, were as follows: NOx= 300 µg/m3 , HC= 54 µg/m3, CO= 350 µg/m3 , PM2.5= 9 µg/m3 , PM Brake= 0.15 µg/m3 and CO2= 2.04*104 µg/m3 which may often be the reason for the black cloud appearing over Erbil’s city center.